Mechanical and microstructural studies in a polysaccharide-acrylate double network hydrogel - Torris, Arun; Nair, Sanoop; Mol, K. P. Raji; Sengupta, Poulomi; Badiger, Manohar (Journal of the Mechanical Behavior of Biomedical Materials, 2021)
Polymeric hydrogels continue to find a wide range of applications. However, a major drawback of hydrogels is the lack of mechanical strength. In this regard, ``Double Network Hydrogels'' (DN) have shown great promise recently. The toughness in DN hydrogels originates from the synergistic effect of two polymeric networks. In this work, we have synthesized a DN hydrogel consisting of a tightly cross linked carboxymethylcellulose (CMC) as the first network and loosely cross linked poly(hydroxyethylacrylate) (PHEA) as a second network (CMC-PHEADN). The required flexibility in the second network (PHEA) was induced by the presence of a small amount of stearyl methacrylate (SM) as a co-monomer in hydroxyl ethyl acrylate (HEA). The compressive strength of the CMC-PEHA-DN hydrogel was found to be 280 times more than that of CMC-SN hydrogel, and the presence of SM in DN hydrogels showed better recovery after deformation. Cell viability studies showed the biocompatibility of DN hydrogels. The micro-structural analysis of DN xerogels by 3D X-ray Microtomography indicated the presence of oriented pores in size range of 30-40 mu m. To the best of our knowledge, Microtomography was used for the first time to study the DN gels. These hydrogels can be used to develop implants that can withstand prolonged stress and expand the life span of implants.
Keywords: Carboxymethyl cellulose; Double network hydrogels; Poly(hydroxyethyl acrylate); Poly(hydroxyethyl-co-stearyl methacrylate)